2021
DOI: 10.3390/ijms22115499
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cholinergic Markers and Characterization of Splice Variants during Ontogenesis of Rat Dorsal Root Ganglia Neurons

Abstract: Dorsal root ganglia (DRG) neurons synthesize acetylcholine (ACh), in addition to their peptidergic nature. They also release ACh and are cholinoceptive, as they express cholinergic receptors. During gangliogenesis, ACh plays an important role in neuronal differentiation, modulating neuritic outgrowth and neurospecific gene expression. Starting from these data, we studied the expression of choline acetyltransferase (ChAT) and vesicular ACh transporter (VAChT) expression in rat DRG neurons. ChAT and VAChT genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…The present data reinforce previous results obtained by our research group, reaffirming that acetylcholine, probably released in extra-synaptic regions of motor and sensory axons [38], may significantly contribute to Schwann cell development and plasticity through the activation of different cholinergic receptor types. In this study, we assessed the expression of the α7 nAChR in Schwann cells after peripheral nerve injury and proved that the selective activation of this receptor subtype may be relevant to the establishment of the microenvironment favorable to improving nerve regeneration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The present data reinforce previous results obtained by our research group, reaffirming that acetylcholine, probably released in extra-synaptic regions of motor and sensory axons [38], may significantly contribute to Schwann cell development and plasticity through the activation of different cholinergic receptor types. In this study, we assessed the expression of the α7 nAChR in Schwann cells after peripheral nerve injury and proved that the selective activation of this receptor subtype may be relevant to the establishment of the microenvironment favorable to improving nerve regeneration.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies were conducted in the peripheral nervous system where the cholinergic receptors have been identified in SCs, revealing that glial cells are able to respond to cholinergic stimuli [11,12,37]. Interestingly, ACh is present in sciatic nerves and can be potentially released in extrasynaptic regions both by motor and sensory axons [38], suggesting its involvement in axon-glia crosstalk. However, when isolated by the axons and cultured in vitro, SCs are able to synthesize and release ACh that may be useful to contribute to the balance between the proliferative and differentiative phase [39].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ChAT gene expression levels were decreased in both approaches, which may be due to posttranscriptional regulation in process of maturation [55]. These findings were also observed in rats by Corsetti et al [53]. As ChAT is not expressed in the upper MNs, this may suggest successful NPC differentiation into mature and functional lower MNs [52,56].…”
Section: Discussionsupporting
confidence: 65%
“…ChAT is crucial for the synthesis of the neurotransmitter acetylcholine and is selectively expressed in MNs of the spinal cord [3]. Several studies found that ChAT-positive neurons possess electrophysiological activity [27,46,[52][53][54]. On protein level, ChAT was detected in both approaches by flow cytometry and immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%